Reworking the political in digital forests: The cosmopolitics of socio-technical worlds. Issue 1 (December 2022) - Gabrys, Jennifer; Westerlaken, Michelle; Urzedo, Danilo; Ritts, Max; Simlai, Trishant
Forests are increasingly central to policies and initiatives to address global environmental change. Digital technologies have become crucial components of these projects as the tools and systems that would monitor and manage forests for storing carbon, preserving biodiversity, and providing ecosystem services. Historically, technologies have been instrumental in forming forests as spaces of conservation, extraction, and inhabitation. Digital technologies build on previous techniques of forest management, which have been shaped by colonial governance, expert science, and economic growth. However, digital technologies for achieving environmental initiatives can also extend, transform, and disrupt these sedimented practices. This article asks how the convergence of forests and digital technologies gives rise to different socio-technical formations and modalities of "political forests." Through an analysis of five digital operations, including 1) observation, 2) datafication, 3) participation, 4) automation, and 5) regulation and transformation, we investigate how the co-constitution of forests, technologies, subjects, and social life creates distinct materializations of politics–and cosmopolitics. By building on and expanding the concept of cosmopolitics, we query how the political is designated through digital forest projects and how it might be reworked to generate less extractive environmental practices and relations while contributing to more just and pluralistic forest worlds.